The portuguese households' indebtedness - Alves, José (2017)
Since the 2008's nancial crisis authorities have been particularly aware about the necessity of being provided with early warning indicators regarding nancial stability. In fact, the Basel Committee on Banking Supervision suggests the analysis of the difference between the private sector credit-to-GDP ratio and its own long-term trend. For the past two decades Portugal, has witnessed a dramatic indebtedness increase among household. Our objective is to examine the reasons for this increase by analysing the ratio of domestic credit to the private sector to GDP between 1961 and 2011. The main conclusions are the non-suitability of the Basel Committee on Banking Supervision approach for Portugal and the break of the link between deposits and credit from 1992 onwards.